Threshold effects in the 10B(p,α)7Be, 12C(p,γ)13N and 14N(p,γ)15O reactions - Wiescher, M.; R.J. deBoer ,; Görres , J. (Frontiers in Physics, 2022)
The typical energy range for charge particle interactions in stellar plasmas corresponds to a few 10's or 100's of keV. At these low energies, the cross sections are so vanishingly small that they cannot be measured directly with accelerator based experimental techniques. Thus, indirect studies of the compound structure near the threshold are used in the framework of reaction models to complement the direct data in order to extrapolate the cross section into the low energy regime. However, at the extremely small cross sections of interest, there maybe other quantum effects that modify the such extracted cross section. These may result from additional nuclear interactions associated with the threshold itself or could be due to other processes, such as electron screening. Measurements in plasma environments like at the OMEGA or NIF facilities offer an entirely new set of experimental conditions for studying these types of reactions, often directly at the energies of interest. In this paper, we examine three reaction, 10B(p,alpha)7Be, 12C(p,gamma)13N and 14N(p,gamma)15N, which have all be measured at very low energies using accelerator based methods. All three reactions produce relatively long-lived radioactive nuclei, which can be collected and analyzed at plasma facilities using a variety of collection and identification techniques.